ANALISIS KEPUASAN PETANI PADI PENGGUNA LAYANAN JASA ALAT MESIN PERTANIAN DI KABUPATEN BANYUWANGI (Analysis Of Rice Farmers Satisfaction Users Of Agricultural Machinery Services In Banyuwangi District) - PRASETYO, EDO KRESNO; RAHMAN, RENA YUNITA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2024)
The study aims to measure the quality of service performance and measure the level of farmer satisfaction with UPJA Tani Makmur services. The sampling technique used is purposive sampling as many as 34 farmers have used UPJA services more than twice. The variables used in the study are five dimensions of service where each dimension has four variable attributes that will be assessed using a Likert scale based on the level of importance and performance level. The analytical tool used to determine the level of service quality of UPJA Tani Makmur is Important Performance Analysis (IPA) with the help of a Cartesian diagram. To determine the level of farmer satisfaction using the Customer Satisfaction Index (CSI). The results showed that the attribute of giving bonuses or gifts (A18) had the lowest level of conformity and there were three attributes that entered quadrant I (Main priority). The value of the level of farmer satisfaction with UPJA Tani Makmur services in general gets a value of 79.90 where the value is in the "Very Satisfied" criteria.